HOW DO SUSTAINABILITY AND SIZE SUPPORT HOTEL PERFORMANCE? A STUDY IN INDONESIA - Agung, Chris Petra; Debby, Teresia; Melinda, Chatherine (Bina Ekonomi, 2025)
Hotels are one of the sectors that consume a tremendous amount of resources within the tourism industry. Therefore, sustainability becomes one of the concerns that needs to be taken care of. One way to communicate sustainability practices is through a Sustainability Report (SR). Previous studies on how SR affects a company’s performance show inconsistent results. Some also show that other financial factors may determine hotel companies’ performance. This research aims to analyze the effect of SR, liquidity, and firm size on Indonesian hotel companies’ performance during 2020-2022. The data is gathered through annual reports and SR published on the Indonesia Stock Exchange (BEI) website. The analysis is done through descriptive statistics and multiple regression. Statistics show that SR reporting in Indonesian hotel companies is less prevalent. Regression results show that SR, liquidity, and firm size simultaneously and positively influence performance, while partially only firm size positively affects performance. In other words, SR and liquidity should be combined with excellent firm size to impact performance positively.